2019
DOI: 10.1590/1806-9282.65.3.336
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of lncrna uca1 as a diagnostic and prognostic biomarker for ovarian endometriosis

Abstract: SUMMARY OBJECTIVE: Ovarian endometriosis seriously affects the quality of life of females, and long non-coding RNA lncRNA urothelial carcinoma-associated 1 (UCA1) plays pivotal roles in the pathogenesis of various ovarian diseases. However, the involvement of lncRNA UCA1 in ovarian endometriosis remains unknown to date. Therefore, the present study aims to study the role of UCA1 in ovarian endometriosis. METHODS: A total of 98 patients with ovarian endometriosis and 28 healthy females were included. The expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 10 publications
0
22
0
1
Order By: Relevance
“…Notably, serum levels of UCA1 on the day of discharge were remarkably lower in patients with recurrence compared with patients without recurrence. Based on these results, authors concluded that UCA1 participates in the pathogenesis of ovarian endometriosis and may be a putative diagnostic and prognostic marker for this condition (76). Tables 5, 6 show up-and down-regulated lncRNAs in the endometriotic samples, respectively.…”
Section: Lncrnas and Endometriosismentioning
confidence: 85%
See 1 more Smart Citation
“…Notably, serum levels of UCA1 on the day of discharge were remarkably lower in patients with recurrence compared with patients without recurrence. Based on these results, authors concluded that UCA1 participates in the pathogenesis of ovarian endometriosis and may be a putative diagnostic and prognostic marker for this condition (76). Tables 5, 6 show up-and down-regulated lncRNAs in the endometriotic samples, respectively.…”
Section: Lncrnas and Endometriosismentioning
confidence: 85%
“…However, another study has reported downregulation of miR-451 in the eutopic endometrial tissues of patients with endometriosis compared with control tissues ( 53 ). The lncRNA UCA1 has been reported to be up-regulated in ectopic endometrium tissues compared with paired eutopic endometrium tissues in the majority of patients using qRT-PCR ( 76 ). On the other hand, a microarray analysis showed down-regulated of this lncRNA in ovarian ectopic endometrial tissue compared with paired eutopic endometrial tissue ( 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs also exert a regulatory effect on the pathogenesis process of endometriosis. For example, the lncRNA UCA1 and lncRNA CCDC144NL‐AS1 were involved in the pathogenesis of ovarian endometriosis, whereas lncRNA MALAT1 was showed upregulation in ectopic endometrial tissues 8–10 . These researches indicated the regulatory role of lncRNAs in endometriosis.…”
Section: Introductionmentioning
confidence: 88%
“…[4][5][6][7] Many researchers have discovered that lncRNA may play an important role in regulated genes expression and the progression of endometriosis. [8][9][10] Huang et al reported that lncRNA UCA1 was downregulated in endometriosis, 9 and Zhu et al showed an effect of lncRNA BANCR on endometriosis through the ERK/MAPK pathway. 11 Therefore, more attention should be paid to lncRNAs in the study of progression of endometriosis.…”
Section: Introductionmentioning
confidence: 99%